Zakat Management Training Management in Improving Amil Competence - Fadlan, Nur; Rosa, Ade Tutty R.; Tejawiani, Ida; Mulyanto, Agus (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
This research is motivated by the potential of zakat in Indonesia of Rp 327 trillion per year, but the current collection is still Rp 33 trillion per year. This means that only 10.09% of the potential collection is carried out by OPZ (Zakat Management Organization). One of the important pillars in zakat management is amil zakat, so this study aims to describe and analyze the management of zakat management training in improving the competence of amil. This study uses George Robert Terry's management theory and management functions. This study also uses the Kirkpatrick Model in program evaluation formulated by Donald Kirkpatrick. This study uses a descriptive qualitative approach with a case study method, data collection techniques with interviews, observation and documentation. The technical analysis of this research data uses data reduction, data presentation, conclusion drawing and data verification. The results of this study are the planning, organization and implementation of zakat management training in improving the competence of amil at the zakat management training institution are in accordance with the elements in improving the competence of amil. Evaluation of zakat management training at zakat management training institutions only conducted reaction evaluation and learning evaluation. Behavior evaluation and outcome evaluation have not been conducted by zakat management training institutions. The conclusion in this study is that the management of zakat management training at zakat management training institutions is in accordance with the principles of GR. Terry management and is based on the value system of Sanusi so that it can improve the competence of amil, but there are still some shortcomings in the evaluation of the Kirkpatrick Model program, especially behavioral evaluation and outcome evaluation.